A search for new supernova remnant shells in the Galactic plane with H.E.S.S. - Abdalla, Hassan; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Wagner, Stefan; Cologna, Gabriele; Hofmann, Werner (Astronomy and astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV γ-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534−571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614−518 and HESS J1912+101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.